2003
DOI: 10.1536/jhj.44.735
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Imidapril and TA-606 on Rat Dilated Cardiomyopathy After Myocarditis

Abstract: SUMMARYFor the management of chronic heart failure, both angiotensin converting enzyme inhibitors (ACEI) and angiotensin II type1 receptor blockers (ARB) are useful, however, the differences between the two groups of agents are unclear. We compared the effects of long-term treatment with an ACEI (imidapril) and an ARB (TA-606) in rats that had recovered from experimental autoimmune myocarditis (EAM). Forty-two Lewis rats were immunized with porcine cardiac myosin on day 0 and divided into 6 groups, group C (di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…25 We previously showed that long-term treatment with angiotensin-converting enzyme inhibitor and angiotensin receptor blocker attenuated LV remodeling via decreased LV fibrosis with the same model used in this study. 26 It has been known that ANP exerts a direct antifibrotic effect in the myocardium by inhibition of the cardiac rennin-angiotensin-aldosterone system. 6 Thus, although increased capillary density might be expected as one of the beneficial mechanisms in this study, we cannot exclude a potential contribution of direct effects of carperitide on the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…25 We previously showed that long-term treatment with angiotensin-converting enzyme inhibitor and angiotensin receptor blocker attenuated LV remodeling via decreased LV fibrosis with the same model used in this study. 26 It has been known that ANP exerts a direct antifibrotic effect in the myocardium by inhibition of the cardiac rennin-angiotensin-aldosterone system. 6 Thus, although increased capillary density might be expected as one of the beneficial mechanisms in this study, we cannot exclude a potential contribution of direct effects of carperitide on the myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] We have been interested in proteins that correlate well with the progression of EAM-induced heart failure. In the present study, we conducted a proteomic analysis to specify and identify proteins which correlate well with the changes in cardiac function in the chronic phase of heart failure.…”
mentioning
confidence: 99%